2016
DOI: 10.1186/s12958-016-0175-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of embryo morphology and morphometrics on implantation of vitrified day 3 embryos after warming: a retrospective cohort study

Abstract: BackgroundCharacteristics routinely used to evaluate embryo quality after thawing include number of blastomeres survived and presence of mitosis resumption after overnight culture. It is unknown to which extent symmetry and fragmentation affect implantation after warming and whether application of stricter criteria either before vitrification or after warming would improve implantation rate (IR) of vitrified/warmed embryos. This study aimed to find new parameters to improve selection criteria for vitrification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The presence of asymmetrical blastomeres and the % fragmentation in fresh cleavage stage embryos have been negatively correlated with implantation rate (IR) [ 9 ] and positively correlated with the incidence of aneuploidy [ 24 27 ]. However, using a computer based morphometric analysis –that calculates both embryo symmetry and fragmentation based on individual blastomere volume and total cell volume (TCV) [ 28 ] –we did not observe any effect of neither symmetry (>50%) nor fragmentation (<40%) on IR in FET [ 29 ]. Yet, due to the fact that cryopreservation media cause exchange of water and medium through the cell membrane [ 8 , 30 ] and because of the different concentration of cryoprotectants present in slow freezing and vitrification media [ 30 ], we hypothesize that TCV might influence differently the survival of slow frozen-thawed embryos than of vitrified-warmed embryos.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The presence of asymmetrical blastomeres and the % fragmentation in fresh cleavage stage embryos have been negatively correlated with implantation rate (IR) [ 9 ] and positively correlated with the incidence of aneuploidy [ 24 27 ]. However, using a computer based morphometric analysis –that calculates both embryo symmetry and fragmentation based on individual blastomere volume and total cell volume (TCV) [ 28 ] –we did not observe any effect of neither symmetry (>50%) nor fragmentation (<40%) on IR in FET [ 29 ]. Yet, due to the fact that cryopreservation media cause exchange of water and medium through the cell membrane [ 8 , 30 ] and because of the different concentration of cryoprotectants present in slow freezing and vitrification media [ 30 ], we hypothesize that TCV might influence differently the survival of slow frozen-thawed embryos than of vitrified-warmed embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, due to the fact that cryopreservation media cause exchange of water and medium through the cell membrane [ 8 , 30 ] and because of the different concentration of cryoprotectants present in slow freezing and vitrification media [ 30 ], we hypothesize that TCV might influence differently the survival of slow frozen-thawed embryos than of vitrified-warmed embryos. Using morphometric evaluation we have previously shown that, indeed, vitrification can induce both an increase or decrease of TCV after warming, [ 29 ] and in fresh cycles, TCV has been associated with IR [ 28 ]. Currently, the effect of morphometric parameters on survival and IR after cryopreservation is still unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations